Wickham striae on skin appendages: a helpful dermoscopic feature - Laura Fagotto; Laura Gnesotto; Colombina Vincenzi; Bianca Maria Piraccini; Luigi Naldi; Andrea Sechi (PAGEPress Publications, 2023)
Lichen planus (LP) is a chronic inflammatory disease, clinically characterized by purpuric, itchy papules that typically spread on the trunk and extremities. Other body sites can also be affected, including mucosal membranes, nails, and the scalp. The use of dermoscopy is essential in determining the diagnosis of LP, as it may highlight pathognomonic features such as Wickham striae (WS). WS are thin, pearly white structures arranged in a reticular pattern that are observed over LP lesions and histologically correspond to epidermal hypergranulosis. WS is usually most visible on the oral mucosa but can also cover almost every active LP papule. Here, we report two cases of biopsy-proven LP that show WS on dermoscopy in two specific sites: the scalp and proximal nail fold.